Validation of the Argentine version of the Montreal Cognitive Assessment Test (MOCA): A screening tool for Mild Cognitive Impairment and Mild Dementia in Elderly - Serrano, Cecilia M. (Dement Neuropsychol, 2020)
The MoCA is a brief useful test to diagnose mild cognitive impairment (MCI) and mild dementia (MD). To date, no Argentine cross-cultural adapted validations of the Spanish version have been reported. OBJECTIVE: To validate the MoCA in the elderly and study its usefulness in MCI and MD. METHODS: This study included 399 individuals over 60 years old evaluated in the Cognitive-Behavioral Department (2017-2018). Patients with<3 years of education, sensory disturbances, psychiatric disorders, or moderate-severe dementia were excluded. The control group comprised cognitively normal subjects. Participants were classified according to neuropsychological assessment and clinical standard criteria into Control, MCI or MD groups. A locally adapted MoCA (MOCA-A) was administered to the patients and controls. RESULTS: Mean educational level was 10.34 years (SD 3.5 years). MoCA-A score differed significantly among groups (p<0.0001). MoCA-A performance correlated with educational level (r: 0.406 p<0.00001). Adopting a cut-off score ≥25 (YI=0.55), the sensitivity for MCI was 84.8% and for MD ​​100%, with specificity of 69.7%. When adding a single point to the score in patients with ≤12 years of education, the specificity of the test reached 81%. CONCLUSION: The MoCA-A is an accurate reliable screening test for MCI and MD in Argentina.